Leveraging a new Rosetta Stone: Deciphering human + technical skills to navigate the future of work. Issue 2 (29th April 2019) - Weise, Michelle R.
Abstract: The most valuable workers now and in the future will be those who can combine technical knowledge with human skills and adapt to the changing needs of the workplace.